Dynamic Competition in Space: Theoretical Models, Empirical Evidence, Political Challenges. - Paqué, Karl-Heinz (Springer, 2018)
The paper delivers a brief summary of what growth and structural change of the global economy as well as technological and demographic trends mean for urban agglomerations and rural areas in Europe. It covers theoretical models, empirical evidence and political challenges. Its main conclusion is that, at least in Europe, the time of natural convergence of regions in geographical space is over as the knowledge-based economy of the future favors innovative centers over the periphery. As a consequence, competition between urban growth poles in space will become ever more intense, and a traditional egalitarian regional policy ever more difficult. This may raise the level of economic and political tensions within the European Union and within individual member countries. The debt crises of southern European countries, the rise of populist movements as well as the recent referenda in the United Kingdom on Scottish Independence and Brexit may be first cases in point. Therefore, a thorough redesign of regional policy tools is called for: away from physical to intellectual infrastructure that fosters innovative capacity.
Keywords: Regionalentwicklung; Regionalpolitik; Stadt; Innovation; Wettbewerb; Wirtschaft; Stadtökonomie; Wirtschaftswachstum; Wirtschaftsstandort